Heparin modulates chemokines in human endometrial stromal cells by interaction with tumor necrosis factor α and thrombin - Spratte, Julia; Schönborn, Magdalena; Treder, Nora; Bornkessel, Frauke; Zygmunt, Marek; Fluhr, Herbert (Fertility and sterility, 2015)
Objective - To study the impact of heparins on chemokines in decidualized human endometrial stromal cells (ESCs) in vitro. - Design - In vitro experiment. - Setting - Research laboratory. - Patient(s) - Premenopausal women undergoing hysterectomy for benign reasons. - Intervention(s) - ESCs were isolated from hysterectomy specimens, decidualized in vitro and incubated with unfractionated heparin and low-molecular-weight heparins (LMWHs) as well as tumor necrosis factor (TNF) α or thrombin with or without heparins. - Main Outcome Measure(s) - Chemokines CXCL1, CXCL5, CXCL8, CCL2, and CCL5 were measured with the use of ELISA, and CXCL5, CXCL8, CCL2, and CCL5 were detected with the use of real-time reverse-transcription polymerase chain reaction. Cell viability was determined with the use of a fluorometric assay. - Result(s) - TNF-α and thrombin stimulated distinct patterns of chemokines in ESCs. Unfractionated heparin and LMWHs attenuated the TNF-α-mediated induction of CXCL8 and enhanced CXCL5, CCL2, and CCL5. The stimulating effect of thrombin on CXCL8 could be inhibited by heparin, whereas heparin had no impact on thrombin-induced CXCL1 and CCL2. Nuclear factor of transcription κB signaling mediated the effects of TNF-α. The effects of thrombin were mediated via extracellular signal-regulated protein kinases 1/2. - Conclusion(s) - Heparins have modulating effects on TNF-α- and thrombin-induced endometrial chemokines, which might have implications in the regulation of endometrial receptivity and early implantation.
Gesehen am 22.06.2020